2013
DOI: 10.5858/arpa.2011-0466-oa
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Novel Molecular Assay Examining the Role of Aminopeptidase P Polymorphisms in Acute Hypotensive Transfusion Reactions

Abstract: N Context.-Acute hypotensive transfusion reactions are potentially harmful adverse effects of transfusion attributable to bradykinin generation. They are most often seen in patients taking angiotensin-converting enzyme (ACE) inhibitors (ACE-Is) because of the role ACE plays in metabolizing bradykinin. However, a number of acute hypotensive transfusion reactions occur in patients not taking ACE-Is. Aminopeptidase P (APP), another important enzyme responsible for bradykinin degradation, is encoded by the polymor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…This increase in BK levels was thought to be most likely caused by reduced BK elimination due to exclusion of the lungs as the main site of BK metabolism and less likely related to increased production through contact system activation . Supporting the concept of abnormal BK metabolism as the cause of HyTRs during CABG, a recent study demonstrated that two of three patients not receiving ACEi who had undergone CABG and developed HyTRs were found to have a single‐nucleotide polymorphism of the APP gene, the C‐2399A, which results in decreased APP activity . Taken together with this study, these findings suggest that situations resulting in increased BK levels, such as altered metabolism for bypassing the lungs or the presence of a polymorphism that results in decreased enzyme activity, can predispose patients to develop an acute episode of hypotension after transfusion of a blood component.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This increase in BK levels was thought to be most likely caused by reduced BK elimination due to exclusion of the lungs as the main site of BK metabolism and less likely related to increased production through contact system activation . Supporting the concept of abnormal BK metabolism as the cause of HyTRs during CABG, a recent study demonstrated that two of three patients not receiving ACEi who had undergone CABG and developed HyTRs were found to have a single‐nucleotide polymorphism of the APP gene, the C‐2399A, which results in decreased APP activity . Taken together with this study, these findings suggest that situations resulting in increased BK levels, such as altered metabolism for bypassing the lungs or the presence of a polymorphism that results in decreased enzyme activity, can predispose patients to develop an acute episode of hypotension after transfusion of a blood component.…”
Section: Discussionsupporting
confidence: 77%
“…8 Supporting the concept of abnormal BK metabolism as the cause of HyTRs during CABG, a recent study demonstrated that two of three patients not receiving ACEi who had undergone CABG and developed HyTRs were found to have a single-nucleotide polymorphism of the APP gene, the C-2399A, which results in decreased APP activity. 9 Taken together with this study, these findings suggest that situations resulting in increased BK levels, such as altered metabolism for bypassing the lungs or the presence of a polymorphism that results in decreased enzyme activity, can predispose patients to develop an acute episode of hypotension after transfusion of a blood component. However, the ultimate mechanism that precipitates a hypotensive episode upon transfusion of blood components is still unclear.…”
Section: Discussionsupporting
confidence: 65%
“…1,10,11 Most studies of XPNPEP2 focused on its effects in the cardiovascular system; for example, XPNPEP2 inactivates bradykinin, and a variant in XPNPEP2 was associated with ACE inhibitor-induced angioedema. 12 However, no studies have explored the relationship between XPNPEP2 and the occurrence and progression of cancer. Our data demonstrated for the first time that XPNPEP2 expression was significantly higher in CC tissue samples than in normal and CIN tissue samples.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that the polymorphism of the APP gene is related to the occurrence of ACE inhibitor-associated angioedema (7,8). It should be noted that the same polymorphism has been also demonstrated to correlate with the occurrence of acute hypotensive transfusion reaction (9).…”
Section: Discussionmentioning
confidence: 97%